Rapid Sequence Induction and Intubation: A Narrative Review - Valeria Martínez-Hurtado; Mateo Aristizábal-Hincapié; Mario Andrés Zamudio-Burbano (Iatreia, 2023)
Despite technological advancements and the development of non-technical skills, preventable deaths due to failures in advanced airway management remain an issue in the care of unstable patients. One of the strategies described to enhance first-attempt intubation success rates and potentially reduce complications is rapid sequence induction and intubation, a complex intervention requiring healthcare personnel preparedness. Since its original description, there have been deeper insights, new interventions, and modifications, warranting a synthesis of this evidence. This article presents a narrative review on the topic based on a non-systematic search, resulting in an approach to the most representative actions and interventions according to the authors’ judgment. It emphasizes airway assessment, critical team preparation, appropriate positioning based on population type, preoxygenation strategies, underlying cause pre-stabilization, summary of induction and neuromuscular blocking agents, alternative intubation strategies like videolaryngoscopy, and post-intubation care including the dual vector fixation strategy and initial ventilation parameters.